Achieving Virtual Teamwork Using Software Agents - Whatley, Janice (Proceedings of the International Conference on Networked Learning, 2004)
In this paper a software agent system is described to help give online support to students who are taking part in team projects. A prototype agent system has been designed to help with allocating tasks to students in the team and to assist agreement on ground rules for working together. After two iterations of implementing this agent system with student teams, the findings from student feedback is given, with suggestions for enhancing the functions of the agent system in future prototypes.